The Role of Internal Auditors in Supporting the Implementation of the Principles of Transparency and Accountability (Study at PT. Bank Mega Syariah KC. MEDAN) - Vica Lily Tan Patricia (Journal of Indonesian Management, 2022)
Internal Audit is an independent assessment function made within an organization or company with the aim of testing and evaluating the number of varios activities carried out by the organization or company. With the aim of assisting the management of the organization in providing accountability in an effective form. Internal Audt activities are to provide recommendations and sses in order to improve the governance process of a company (Good Corporate Governance), in order to be able to achieve the goals and targets that have been previously set by te company. In the current era of globalization which has entered the 4.0 era, the developing business world has developed very rapidly. Therefore, in dealing with this, companies/business entities need to improve the implementation of Good Corporate Governance especially on the principles of transparency and accountability. The implementation of this matter is also influenced by the role of the internal auditor. The more the role of the Internal Auditor’s performance in the company, the more application of these two principles will be. This research was conducted at PT. Bank Mega Syariah KC MEDAN. This company is company in a banking service. This research was conducted by taking data from the OJK and the website which focused on the application of the principle of accountability, and the role of internal auditors in supporting the implementation of these two principles. The research indicate that the implementation of the principles of transparency and accountability has beeb going well, and the role of Internal Auditors has supported implementation of these two principles.